A longitudinal comparative study by in vivo harmonic generation microscopy: Q‐switched ruby laser versus picosecond 532‐nm Nd: YAG laser for the treatment of solar lentigines - Pei‐Jhe Wu; Sheng‐Tse Chen; Yi‐Shuan Sheen; Chi‐Kuang Sun; Yi‐Hua Liao (Wiley, 2022)
Abstract Background Nanosecond quality‐switched ruby laser (QSRL) and frequency‐doubled 532‐nm picosecond Nd:YAG laser (532‐nm picosecond Nd: YAG laser [PSNYL]) are well‐documented treatments for solar lentigines (SLs). However, no studies have longitudinally tracked the microscopic findings before and after QSRL and 532‐nm PSNYL treatment for SL removal. Objectives To compare the clinical efficacy and dynamic histological changes between QSRL and 532‐nm PSNYL in the treatment of SLs in Asian patients. Method Twenty‐five patients with SLs on both sides of the face were enrolled in this prospective split‐face study. QSRL and 532‐nm PSNYL therapy for SLs on the left and right side of the face, respectively, were performed for each subject. All subjects underwent baseline and follow‐up assessment at Weeks 3 and 6. In vivo harmonic generation microscopy (HGM) imaging was adopted for the noninvasive observation of melanin mass density of basal cells (MMDbasal cell), epidermal melanocyte dendricity, and dermal melanophages before and after laser treatment. Results At Week 6, 60% of the lesions treated with QSRL and 68% with 532‐nm PSNYL had over 75% improvement. Histologically, both lasers resulted in statistically significant decrease of MMDbasal cell in SLs to the level of that in the normal skin at Weeks 3 and 6. Statistically significant increase of dermal melanophages was observed 3 weeks after both laser treatments. Nevertheless, 532‐nm PSNYL led to faster clearance of melanophages than QSRL at Week 6. Moreover, activated melanocytes with enhanced dendrite formation was significantly increased till 6 weeks after both laser treatments. Conclusion Both QSRL and 532‐nm PSNYL were effective treatments for SLs, and there was no statistically significant difference in clinical scoring. However, from histological aspect, 532‐nm PSNYL was associated with lower degree of melanin incontinence and melanophage accumulation. HGM imaging analysis can noninvasively quantitate the cutaneous response to pigmentary laser therapy.